Evaluating Rural Consumers’ Knowledge and Attitudes toward Digital Service VAT: Evidence from a Philippine Countryside Market - Montiagodo, Jeselle; Hamasaki, Yumi C.; Onsay, Emmanuel A. (New Countryside, 2026)
This study examines the impact of online customers’ knowledge on their attitudes and perceptions towards Republic Act No. 12023, focusing on Value-Added Tax (VAT) for digital services in online sales transactions. Through a causal research design, socio-economic profiles were determined, online customers’ knowledge of R.A. No. 12023 was evaluated, attitudes and perceptions were analyzed, and the influence of knowledge on attitudes and perceptions was assessed. Surveys were conducted online and face-to-face with buyers in a selected municipality in the Partido Area, with data analyzed using an ordinal regression model. Results indicate that a majority of online buyers in the Partido Area possess knowledge of the Digital Services Tax Law, with a higher proportion acknowledging awareness. The study reveals a positive attitude among online buyers towards continuing online purchases despite the Value-Added Tax (VAT) imposition, with most displaying a favorable perception of the Digital Services Tax. Statistical analysis demonstrates that online customers’ knowledge significantly influences their purchasing behavior and perceptions of the VAT on Digital Services Law. In conclusion, this research underscores the crucial role of knowledge in shaping customers’ behaviors and acceptance of VAT on Digital Services. Clear communication and public education efforts are recommended to ensure users understand the law accurately, potentially increasing their acceptance of the policy.